Microbial Debromination of Polybrominated Diphenyl Ethers by Dehalococcoides-Containing Enrichment Culture - Zhao, Siyan; Fan, Siyan; He, Yide; Zhang, Yongjun (Frontiers in Microbiology, 2022)
Polybrominated diphenyl ethers (PBDEs), commonly used as flame retardants in a wide variety of consumer products, are emerging persistent pollutants and ubiquitously distributed in the environment. The lack of proper bacterial populations to detoxify these recalcitrant pollutants, in particular of higher brominated congeners have confounded the attempts to bioremediate PBDE contaminated sites. In this study, we report a Dehalococcoides-containing enrichment culture, PB, which completely debrominates 0.44 uM tetra-BDE 47 to diphenyl ether within 25 days (0.07 uM Br- /day) and extensively debrominates 62.4±4.5% of 0.34 uM hepta-BDE 183 (0.006 uM Br- /day) with predominant generation of penta- through tri-BDEs as well as small amounts of diphenyl ether within 120 days. Enzymatic and molecular analysis suggested the debromination of tetra-BDE 47 and hepta-BDE 183 were catalyzed by different reductive dehalogenases. Later, a marked acceleration rate (0.021 uM Br- /day) and more extensive debromination (87.7±2.1%) of hepta-BDE 183 was observed in the presence of tetra-BDE 47, which is achieved via faster growth rate of responsible bacterial populations on lower BDE-47 and co-metabolic debromination by BDE-47 reductive dehalogenases. This finding is of environmental implications in in situ PBDEs bioremediation since both BDE-47 and BDE-183 are dominant and representative BDE congeners, and often co-exist in contaminated sites.